Mediation of information to combat misinformation in the school (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The text presents preliminary reflections on the mediation of information to combat misinformation in the school environment. As a prerequisite for a study that aims to answer how to combat the spread of fake news that generates misinformation in the school environment? To begin the reflections that aim to seek answers, and based on the literature review, the study of theoretical support was used. The reflection sought to present mediation in the current context of networks, the relationship with information science, aimed at education and web networks; and the possibilities of actions to combat and mitigate the spread of fake news that generate disinformation.
Keywords: information mediation; disinformation; combat misinformation in schools